(untitled) (Research, Society and Development, 2021)
Aim: correlate the level of physical disability with pain, balance and gait in elderly with chronic low back pain. Method: observational study conducted at the Catholic University of Pernambuco. Initially, a lecture was held on the objectives of the study and after signing the Informed Consent Form, sociodemographic data were collected; assessment of the level of physical disability due to pain through Roland-Morris and Oswestry; Pain intensity by visual analog scale (VAS); Balance by Berg Balance Scale and Risk of Tinetti Fall. Results: the sample consisted of 20 elderly, with female predominance (80%), average age of 70.95 ± 6.08 years. There was a significant correlation between physical disability pain level, balance level and risk of falling. Conclusion: It was possible to show in the elderly with low back pain, an association between the questionnaires that assess physical disability. It can be concluded that there was a significant correlation between the level of physical disability with pain intensity and gait. In addition, the relevance of using assessment instruments for the development of therapeutic strategies aimed at autonomy and independence of the elderly person’s health is also emphasized.